(untitled) (Indian Journal of Child Health, 2019)
Background: Administration of prelacteal feeds (PLFs) is a common practice among mothers which has no scientific basis. It israther fraught with disadvantages, particularly to the newborn. It constitutes a major impediment to the commencement of exclusivebreastfeeding which is the foundation for proper infant nutrition. Aim: The objective of this study was to determine the prevalence,types, and reasons for administration of PLF. Materials and Methods: A cross-sectional descriptive study was conducted inthe Well Baby Clinic of a Abia State University Teaching Hospital, Aba, Nigeria. Data on the sociodemographic characteristics,utilization of health services, mode of delivery, and administration of PLF were obtained from mothers. Results: A total of 444mothers were enrolled over the study period, of which 43.2% administered PLF. Cesarean section delivery and women aged29–39 years were significantly associated with PLF administration. Glucose water constituted the predominant PLF administered.Health workers were the most influential factor in the administration of PLF. Delayed lactation constituted the major reason forthe administration of PLF. Conclusion: Sustained education of the populace and the training and retraining of health workers,particularly obstetric staff, could help to curb PLF administration.